LOSS OF FRIENDS AND PSYCHOLOGICAL WELL-BEING OF OLDER CHINESE AMERICANS. (11th November 2018) - Liu, J; Mao, W; Guo, M; Xu, L; Chi, I
Abstract: This study uses data of 3, 159 older Chinese American from PINE and performs multivariate linear and logit regression analyses to test how losing friends in the past five years affected depressive symptoms, loneliness and quality of life. The results show that the older Chinese who had experienced loss of friends reported significantly higher loneliness but better quality of life than the ones without such bereavement experience. The effects of loss of friends on loneliness and quality of life were significantly weaker in the older group aged 80+ than the effects among the younger group aged 59 to 69. The married older Chinese were also more sensitive to loss of friends in terms of loneliness. The findings suggest the importance of loss of friends in shaping psychological well-being of older Chinese Americans. More research is needed to explore the nuanced mechanism of loss of friends and mental health in later life.